SWOT Analysis with IFAS-EFAS Approach: A Case Study of Human Resource Management at Indonesian Customs and Excise - Firul Zubaid Affandi; Risyad Fahri Murfid; Rafli Pratama; Dian Furghoni; Sarinah Sihombing (International Journal Labs, 2026)
This research analyzes the strategic management of human resources (HR) in the Indonesian Customs and Excise Organization through the integration of the SWOT method with a quantitative approach using IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary). The study employs a qualitative descriptive methodology based on evidence from academic journals and organizational documents from 2020 to 2025. Through the analysis of 15 academic journals and Customs documents, this research identifies internal strategic factors: strategic mandate (weight 0.20; rating 3.5), merit-based recruitment (0.18; 3.0), competency development (0.17; 3.0), integrity awareness (0.22; 3.5), and technology infrastructure (0.15; 2.5), with a total IFAS score of 2.81. External opportunities include administrative reform (0.20; 3.5), HR technology adoption (0.18; 3.0), integrity standard improvement (0.22; 3.5), national talent pool (0.15; 2.5), and international collaboration (0.15; 2.5). External threats include endemic corruption (0.25; 3.5), geographical challenges (0.22; 3.0), private sector competition (0.20; 3.0), ethical leadership say-do gap (0.18; 2.5), and resistance to change (0.15; 2.0), with a total EFAS score of 2.86. The results of the study show that the IFAS-EFAS-based approach, supported by empirical evidence from journals, produces specific strategic positioning, facilitates objective decision-making, and provides actionable and context-specific TOWS strategy recommendations. The research concludes that the implementation of a holistic approach integrating ethical leadership, merit-based recruitment systems, competency-based human resource development, and digital transformation is the optimal strategy for strengthening the competitive position of the Customs and Excise Organization in the face of multidimensional HR challenges.